OVERALL QUALITY OF URBAN LIFE AND NEIGHBORHOOD SATISFACTION: A Household Survey in the Walled City of Famagusta - Oktay, Derya; Marans, Robert W. (Open House Int, 2010)
This study aims to identify key indicators affecting the residents' perception of overall quality of urban life in the Walled City of Famagusta, the historic core of the city, which reflects a decaying socio-spatial quality. The paper first presents a brief overview of the research methodology and then analyses the results from a household survey carried out in the Walled City, in order to provide a sheer understanding of people's feelings about their neighbourhood environment and the overall urban quality of life in case of implementation of a possible regeneration scheme for the area. The research contributes some empirical evidence to verify the claimed benefits and shortcomings in terms of effects of neighbourhood satisfaction, sense of community, sense of belonging, neighbourhood attributes, use/evaluation of cultural and recreational opportunities and safety on the overall quality of urban life of the residents, as well as to identify the predictors of the neighbourhood satisfaction.
Keywords: Walled City of Famagusta; Quality of Urban Life; Neighborhood Satisfaction; Sense of Neighbourhood As Home; Sense of Belonging; Neighbourhood Attributes; Use/Evaluation of Cultural/Recreational Activities; Safety